Relación del Estado Nutricional con el Desarrollo Cognitivo y Psicomotor de los Niños en la Primera Infancia. (2023)
Gestation, the first years of life and nutritional status are important role in physical, psychosocial, emotional and cognitive development in childhood and adolescence. Different investigations have found a relationship between nutritional status with better cognitive performance, although conversely, malnutrition in these stages can cause imbalances between nutritional needs that could lead to obesity or malnutrition and influence cognitive development. The aim of this article was to review the relationship between nutritional status and cognitive and psychomotor development of children in early childhood. The method was systematic review in the databases ProQuest, Redalyc, Science Direct and Scopus in the years 2013-2018. This article concludes that both the intellectual capacity and the development of fine and gross motor skills depend on the nutritional status of infants and therefore a relationship between nutrition and psychomotor and cognitive development is suggested. © 2019 Fundacion para la difusion neurologica en Ecuador - FUNDINE. All rights reserved.